Simultaneous measurement of glucose blood–brain transport constants and metabolic rate in rat brain using in-vivo (1)H MRS - Du, Fei (Nature Publishing Group, 2012)
Cerebral glucose consumption and glucose transport across the blood–brain barrier are crucial to brain function since glucose is the major energy fuel for supporting intense electrophysiological activity associated with neuronal firing and signaling. Therefore, the development of noninvasive methods to measure the cerebral metabolic rate of glucose (CMR(glc)) and glucose transport constants (K(T): half-saturation constant; T(max): maximum transport rate) are of importance for understanding glucose transport mechanism and neuroenergetics under various physiological and pathological conditions. In this study, a novel approach able to simultaneously measure CMR(glc), K(T), and T(max) via monitoring the dynamic glucose concentration changes in the brain tissue using in-vivo (1)H magnetic resonance spectroscopy (MRS) and in plasma after a brief glucose infusion was proposed and tested using an animal model. The values of CMR(glc), T(max), and K(T) were determined to be 0.44±0.17 μmol/g per minute, 1.35±0.47 μmol/g per minute, and 13.4±6.8 mmol/L in the rat brain anesthetized with 2% isoflurane. The Monte-Carlo simulations suggest that the measurements of CMR(glc) and T(max) are more reliable than that of K(T). The overall results indicate that the new approach is robust and reliable for in-vivo measurements of both brain glucose metabolic rate and transport constants, and has potential for human application.